Adoption of improved modern rice varieties and management practices in Ecuador - Labarta, Ricardo Antonio; Orrego, Mayra; Marín, Diego; García, María Alejandra; Twyman, Jennifer; Andrade, Robert Santiago; Yanez, Fernando; Mendoza, Luis (International Center for Tropical Agriculture, 2017)
This dataset provides a description of rice growers collected in Ecuador between October 2014 and March 2015. The survey was implemented using a structured questionnaire administered among 1,028 households in the main rice production areas of Ecuador. Information collected was provided by household heads (. male or female) and included household and plot level data. Survey information includes household socio-demographic characteristics, rice management practices (e.g. improved variety and other input use, costs, etc.) and rice production and utilization (e.g. yields, prices, etc.). Additional socio-economic context variables were also recorded. The dataset contains numeric, categorical and string variables.